The shadow lines - Ghosh, Amitav (New Delhi : Penguin Books, 2008)
"Opening in Calcutta in the 1960's. Amitav Ghosh's radiant second novel follows two families - one English, one Bengali as their lives intertwine in tragic and comic ways. The narrator, Indian born and English educated, traces events back and forth in time, from the outbreak of World War II to the late twentieth century, through decades of violence in Bengal, observing the ways in which political events invade private lives.
Keywords: Boys -- Fiction; Fiction. -- British -- India